Pendidikan Akhlak dalam Persperktif Al-Qur’an: Studi Kualitatif Pandangan Guru Bahasa Inggris terhadap Moral Siswa - Sharmila Azmita; Muhammad Danil Harahap; Windy Febriani; Ali Imran Sinaga (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
In the era of globalization and digitalization, education is not only required to develop cognitive abilities but also to be responsible for the formation of character and noble morals of students. The phenomenon of moral degradation among adolescents demonstrates the need for the involvement of all teachers, including English teachers, in moral education. This study aims to explore English teachers' views on students' moral behavior in the learning process based on the perspective of Quranic moral values. The study used a qualitative approach with a descriptive qualitative design. The subjects were English teachers at the junior and senior high school levels selected through purposive sampling. Data were collected through semi-structured interviews and documentation studies, then analyzed using interpretive thematic analysis. The results showed that teachers viewed honesty, responsibility, discipline, politeness, and mutual respect as important moral aspects that can be observed and developed in English learning. Quranic values, such as ihsan, exemplary behavior, and respect for others, serve as a normative framework in understanding student behavior. This study concludes that English teachers have a strategic role as moral educators and are able to integrate moral education contextually into language learning to support holistic educational goals.